Self-care Behaviour of Pregnant Women with Gestational Diabetes Mellitus at a Tertiary Care Hospital in Lucknow, India: A Quasi-experimental Study - Mallicka; Abhishek Gupta; Shivendra Kumar Singh; Amita Pandey; Manish Kumar Manar (Journal of Clinical and Diagnostic Research, 2024)
Introduction: India is now the diabetes capital of the world. The rising burden of Gestational Diabetes Mellitus (GDM) adds to the existing diabetes burden. Euglycemia is achieved once the baby is delivered. The first line of management of GDM is mainly through lifestyle modification with diet and physical activity. There is a dearth of information from Lucknow city about how well pregnant women with GDM adhere to dietary changes and exercise recommendations, or how counselling helps them deal with their GDM. Aim: To assess the self-care behaviour related to diet, physical activity, and Self-Monitoring of Blood Glucose (SMBG) of pregnant women diagnosed with GDM. Materials and Methods: A total of 188 pregnant women diagnosed with GDM were selected for present quasi-experimental study. The study participants were recruited from the antenatal Outpatient Department (OPD) at the Department of Obstetrics and Gynaecology of Queen’s Mary Hospital, King George Medical University (KGMU), Lucknow, India. The total study duration was from November 2019 to November 2022. Pregnant women diagnosed with GDM according to Diabetes in Pregnancy Study Group in India (DIPSI) criteria, up to 28 weeks of gestation, who gave their written consent to participate in the study and were living within a 15-kilometer radius of the study Institute, were included in the study. One group of the study participants received one-to-one counselling, an individualised diet plan, along with usual GDM care, and the other group received usual GDM care during their antenatal visits. The summary of diabetes self-care was adapted to assess adherence to the recommended dietary and physical activity modifications, as well as self-monitoring of blood glucose. Data were analysed using R software version 4.1.1 (R Core Team, 2021). All categorical data were presented using frequency and percentages. The comparison of baseline demographic and clinical parameters of pregnant women between the two groups was done using the Chi-square test or Fisher’s-exact test for categorical observations based on the expected frequency. The independent sample t-test or Mann-whitney U test for continuous measurements was used after checking the normality assumption using the Shapiro-wilk test. The change in scores of general diet, specific diet, physical activity, and SMBG throughout all follow-ups was assessed by repeated measures Analysis of Variance (ANOVA). The change from the first follow-up visit to subsequent follow-up visit was compared using a mixed linear model with follow-up visits. The p-value was considered significant at a 5% level of significance for all comparisons. Results: The mean age of the pregnant women with GDM was 27.6±3.7 years in the intervention group and 27.9±3.9 years in the control group (p=0.451). The pregnant women with GDM in the two groups did not show significant differences in terms of socio-demographic variables such as age, religion, education, socio-economic status, occupation, type of family, and family history of diabetes mellitus. A significant difference was observed in the dietary and physical activity scores between the two groups of pregnant women with GDM. However, no difference was observed in the case of self-monitoring of blood glucose scores of the two groups. Conclusion: The study concluded that counseling plays an important role in helping pregnant women with GDM adhere to the recommended dietary modifications and physical activity.